Neonatal exposure to bisphenol A modifies the abundance of estrogen receptor α transcripts with alternative 5′-untranslated regions in the female rat preoptic area - Monje, Lucas Daniel (2007)
The xenoestrogen bisphenol A (BPA) is commonly ingested by humans. We examined the effects of neonatal exposure to low versus high doses of BPA over the control of estrogen receptor alpha (ERalpha) expression in the preoptic area (POA) of prepubertal female rats. Pups received s.c. injections every 48 h of BPA (high dose, 20 mg/kg and low dose, 0.05 mg/kg) or diethylstilbestrol (DES, 0.02 mg/kg) from postnatal day (PND) 1 to PND7 and were killed at PND8 or PND21. Relative expression of ERalpha transcripts containing alternative 5´-untranslated regions OS, ON, O, OT, and E1 in POA were evaluated by RT-PCR. Methylation status of ERalpha promoters was determined by bisulfited DNA restriction analysis and ERalpha protein by immunohistochemistry. In PND8, the high dose of BPA and DES diminished total ERalpha mRNA levels, mediated by the decreased expression of ERalpha-O and ERalpha-OT variants. In contrast, the low dose of BPA augmented total ERalpha mRNA by increasing the expression of the ERalpha-E1 variant. In PND21, both BPA doses increased total ERalpha mRNA by means of the augmented expression of ERalpha-O and ERalpha-OT variants. In PND21, the methylation status of the ERalpha promoters and the circulating levels of estradiol were similar in all experimental groups. At PND8 and PND21, DES and the high dose of BPA decreased, while the low dose of BPA increased ERalpha protein in the POA. These findings show that neonatal BPA exposure alters the abundance of hypothalamic ERalpha transcript variants and protein in a dose-dependent manner.